The Impact of Multimedia on Information Dissemination in the Digital Era - Ahmad Fariza Ari Duan; Febriansyah Febriansyah; Hendri Purnomo (Universitas Islam Al-Azhar Mataram, 2025)
The way people access, manage, and disseminate information has been fundamentally transformed by the rapid advancement of digital technology. Multimedia—integrating text, images, audio, video, and animation into interactive digital formats—is one of the most significant developments. Using a qualitative descriptive approach based on literature review, this study aims to investigate the influence of multimedia on information dissemination in the digital era. The findings indicate that platforms such as TikTok, Google, and WhatsApp have a substantial impact on content consumption and distribution patterns across various age groups. While multimedia can foster creativity and enhance communication, it also poses risks such as misinformation and emotional manipulation. Understanding these dynamics is essential to maximize the potential of multimedia and minimize its drawbacks. This study highlights the critical importance of digital literacy and ethical media use to ensure the flow of accurate and responsible information in society.